Application of DOE to ELISA Robustness and Ruggedness Assessment - Thy Follmer; Seth Clark; Thorsten Verch (The AAPS Journal, 2025)

Analytical Quality by Design, Life Cycle Management, and Method Control - Thorsten Verch; Cristiana Campa; Cyrille C. Chéry; Ruth Frenkel; Timothy Graul; Nomalie Jaya; Bassam Nakhle; Jeremy Springall; Jason Starkey; Jette Wypych; Todd Ranheim (The AAPS Journal, 2022)
Analytical methods are utilized throughout the biopharmaceutical and vaccines industries to conduct research and development, and to help control manufacturing inputs and outputs. These analytical methods should continuously provide quality data to support decisions while managing the remaining of risk and uncertainty. Analytical quality by design (AQbD) can provide a systematic framework to achieve a continuously validated, robust assay as well as life cycle management. AQbD is rooted in ICH guidelines Q8 and Q9 that were translated to the analytical space through several white papers as well as upcoming USP 1220 and ICH Q14. In this white paper, we expand on the previously published concepts of AQbD by providing additional context for implementation in relation to ICH Q14. Using illustrative examples, we describe the AQbD workflow, its relation to traditional approaches, and potential pathways for ongoing, real-time verification. We will also discuss challenges with respect to implementation and regulatory strategies.

Monoclonal Antibody Reagent Stability and Expiry Recommendation Combining Experimental Data with Mathematical Modeling - Malorie Fink; Erin Marie Cannon; Carl Hofmann; Nisarg Patel; Cindy Pauley; Matthew Troutman; Richard R. Rustandi; Mary Shank-Retzlaff; John Loughney; Thorsten Verch (The AAPS Journal, 2020)